2003
DOI: 10.1021/ja0294919
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Thio Acids with Azides:  A New Mechanism and New Synthetic Applications

Abstract: A new amide synthesis strategy based on a fundamental mechanistic revision of the reaction of thio acids and organic azides is presented. The data demonstrate that amines are not formed as intermediates in this reaction. Alternative mechanisms proceeding through a thiatriazoline intermediate are suggested. The reaction has been applied to the preparation of simple and architecturally complex amides that are difficult to access using conventional methods. The reaction is chemoselective, effective for unprotecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
183
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(198 citation statements)
references
References 24 publications
3
183
0
5
Order By: Relevance
“…In their work, Manetsch et al utilise the reaction of a thioacid and sulfonyl azide to generate an amide, a reaction that they proposed as particularly suitable for RAS, Figure 20. [97,98] Figure 20 Mechanism for reaction of a sulfonyl azide with a thioacid to generate an amide, termed the 'sulfo-click' reaction.…”
Section: Bcl-x L -Sulfo-click Reactionmentioning
confidence: 99%
“…In their work, Manetsch et al utilise the reaction of a thioacid and sulfonyl azide to generate an amide, a reaction that they proposed as particularly suitable for RAS, Figure 20. [97,98] Figure 20 Mechanism for reaction of a sulfonyl azide with a thioacid to generate an amide, termed the 'sulfo-click' reaction.…”
Section: Bcl-x L -Sulfo-click Reactionmentioning
confidence: 99%
“…B. das metabolische Glycan-Engineering durch den nichtnatürlichen Kohlenhydratstoffwechsel, [166][167][168] die nichtnatürliche Proteintranslation, [169] die Exprimierung über auxotrophe Organismen, [170] die posttranslationale [171a,b] (Schema 23 B). [174] Darüber hinaus wurde eine RuCl 3 -vermittelte Variante mit hohen Ausbeuten für die Umsetzung auch sterisch gehinderter Azide beschrieben. [175] Auf der Grundlage dieser Reaktion wurden außerdem potenzielle chemoselektive Ligationen von Sulfonamidderivaten entwickelt, obgleich die Anwendung zur Ligation längerer Peptide noch aussteht.…”
Section: Spurlose Staudinger-ligationunclassified
“…In contrast to carboxylic acids, thioacids have been of considerable interest due to their unique reactivity and selectivity in amide bond formations. Various authors [13][14][15][16][17] have reported elegant methods for N-acylation of amines in peptide synthesis. In 2013, Gopi and co-workers [18] used copper(II) acetate as a catalyst for acylation of amines.…”
Section: Introductionmentioning
confidence: 99%